1998
DOI: 10.1177/03635465980260021201
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept For Isokinetic Hamstring: Quadriceps Muscle Strength Ratio

Abstract: Conventionally, the hamstring:quadriceps strength ratio is calculated by dividing the maximal knee flexor (hamstring) moment by the maximal knee extensor (quadriceps) moment measured at identical angular velocity and contraction mode. The agonist-antagonist strength relationship for knee extension and flexion may, however, be better described by the more functional ratios of eccentric hamstring to concentric quadriceps moments (extension), and concentric hamstring to eccentric quadriceps moments (flexion). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
363
6
35

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 416 publications
(427 citation statements)
references
References 24 publications
23
363
6
35
Order By: Relevance
“…The relation between maximum isokinetic torque of the hamstring muscles and maximum isokinetic torque of the quadriceps muscle (H/Q ratio) is a parameter commonly used to describe the muscle balance of the knee joint. 18 The expected value of the H/Q ratio for asymptomatic adults, evaluated by the isokinetic dynamometer, tends to be from 60% to 76%, varying with the angular speed. 19 However, data on this percentage in the elderly population are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between maximum isokinetic torque of the hamstring muscles and maximum isokinetic torque of the quadriceps muscle (H/Q ratio) is a parameter commonly used to describe the muscle balance of the knee joint. 18 The expected value of the H/Q ratio for asymptomatic adults, evaluated by the isokinetic dynamometer, tends to be from 60% to 76%, varying with the angular speed. 19 However, data on this percentage in the elderly population are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations determined the eccentric peak torque for hamstrings to concentric quadriceps during fast knee extension. Aagaard et al [14,21] reported that functional H/Q increased above 100% with rising velocity and more extended knee joint positions. similarly, Gerodimos et al [27] demonstrated that this functional ratio increased with the growth of angular velocity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, schiltz et al [28] revealed the results of functional H/Q at 30 deg · s -1 /240 deg · s -1 velocities to be approximately 131% (dominant limb) and approximately 126% (non-dominant limb) in professional players. Thus, the functional H/Q > 100% during fast knee extension indicated the ability of eccentrically acting hamstrings to produce a braking joint flexor moment greater than the joint extensor moment exerted by the quadriceps [14,16,21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations